Alterações ambientais dependentes e independentes da resposta: uma investigação dos efeitos de contigüidade versus contingência - Nogara, Thaís Ferro (2006)
The effects of presenting stimuli that are well established as reinforcers independently of responding have been studied under two different perspectives. On the first perspective, through a procedure called accidentally reinforcement, stimuli are presented non-contingently, resulting in the accidental selection of a response, an effect called superstition. On the other perspective, in a procedure called uncontrollability stimuli are presented independently of responding resulting in a difficulty in learning when another contingency is presented, a behavioral effect called learned helplessness (LH). It has been suggested that the interval from the non-contingent presentation of the stimulus and the response may have an important role in producing either one of two behavioral effects. The goal of this study was to investigate: (a) the effects of different duration of an aversive auditive stimuli on the possibility of establishing contiguity between responding and the ending of the stimulus; (b) the effects of the different stimulus-response intervals on the responding pattern; (c) the effects of different manipulations of stimuli presentation (response dependent, response independent, and delayed dependent) on the participants performances in a new escape contingency. Fifty participants were assigned to five groups: contingent (CON), yoked non-contingent (YNC), non-contingent (NC), contingent with delay (CD), and control. Four groups were exposed to two experimental phases: training and testing. In the training phase, each group experienced a different contingency: CON participants could escape from the aversive stimuli; YNC participants experienced the same aversive stimuli (order and duration) as CON participants, but could not escape; NC participants experienced 5s stimuli along the training phase and could not turn them off; CD participants could escape from the stimuli, but the emission of the response started a delay that was dependent upon the interval between the end of the stimulus and the preceding response emitted by a NC participant. The control participants were not exposed to a training phase. During test, all participants could escape from the aversive stimuli by emiting a new escape response. Results show that: a) 12 out of 40 participants showed some accidentally selected behavioral pattern during training. In the testing phase, all this 12 participants learned the new escape response. Other twenty-four participants had their performance in the testing phase classified as learned helplessness: 13 from NC and YNC groups, 4 from CON, 4 from control and 2 from CD; b) stimulus duration did not seem to determine the interval between the end of the stimuli and the preceding response; c) for some participants, temporal contiguity between the end of the stimulus and the preceding response was enough to select a behavioral pattern, but the contingent relation between these two events was a powerful variable in the selection and maintenance responding, even for those participants who were exposed to a contingent but not contiguous (delayed) stimuli-response relation